An intercultural study of refusal strategies in English between Jordanian EFL and Malay ESL postgraduate students - Yasser Al-Shboul; Marlyna Maros; Mohamad Subakir Mohd Yasin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This intercultural communication study investigates the similarities and differences of the speech act of refusals in English between Jordanian English as a Foreign Language (EFL) and Malay English as a Second Language (ESL) postgraduate students. Data were collected using a modified version of the Discourse Completion Test (DCT) initially developed by Beebe, Takahashi and Uliss-Weltz (1990). To obtain responses as natural as real-life communication, an interviewer audiotaped and read the situations aloud to both groups in English to enable the participants to respond verbally to situations. Next, the audiotaped responses obtained from both groups of participants were transcribed with broad transcription convention. Data were analysed in terms of semantic formulaic sequences and were categorized by four trained coders based on the classification of refusal strategies established by Beebe et al. (1990). Results revealed that both groups used almost similar strategies with similar frequency in performing refusals. For example, the most frequently used refusal strategies by the Jordanian and Malay participants were excuse, reason, explanation, and expressing statement of regret. However, they differed in the use and frequency count of indirect strategies with the Malays using less indirect strategies than the Jordanians. In addition, the results indicate that the Jordanian participants expressed ‘gratitude’ less frequently than the Malay participants when refusing invitations by equal and lower status person. Similar results were found when performing refusal in all request situations. The results are expected to be useful in studies in intercultural comparisons.